Estimation of evaporation rates in the north west Arabian gulf based on sea surface temperature and Meteorological data - J. Mohammed Alfartusi, Adel (University of Thi-Qar Journal of Science, 2019)
Bulk aerodynamic formula (Singh's equations) was used to study the evaporation in the north west Arabian gulf. Evaporation was estimated for the region. The annual averages of evaporation in the area are (mm /yr) for two years (2014-2015) 23, 22 respectively. Evaporation is higher in the region during June, July, August, September and October. The correlation between the humidity gradient (ew-ea) and monthly averages of evaporation were high in all regions being approximately 0.8, whereas the correlation between monthly averages of evaporation and wind speed were about 0.6. The main cause of higher evaporation was the humidity gradient (ew-ea), i.e., higher humidity gradient. These variations were related to the changes in humidity and the wind speed at this location.